A Concept-based Approach to the Instruction of the Chinese ba-construction. (24th February 2021) - Ai, Haiyang
Abstract : This study explores a concept-based instruction approach to promoting second languagedevelopment of the ba-construction, a known difficult area, by six collegelevelEnglish learners of Chinese in a two-month enrichment program. We developedSCOBAs to explain the syntactic, semantic, and pragmatic constraints of the baconstruction, as well as its similarities and differences from the canonical Subject-Verb-Object (SVO) and topicalization Object-Subject-Verb (OSV) word orders. Theparticipants' productive use of the construction was assessed with two translations(one on paper and one on the computer) and a cartoon description task followinga pretest, posttest, and delayed posttest format. Semi-structured interviews and theparticipants' verbalization data were also collected. By comparing the participants'gain scores in relation to maximum possible scores, we found that the participants had made large gains throughout the study and retained much of the gain two weeks after the posttest. The microgenetic analyses of the participants' production data showed improvement in the use of resultative verb compound, perfective marker–le, and the placement of directional particles. Finally, the verbalizations data indicated improvement in conceptual understanding of the ba-construction in terms of its scope, i.e., not just the physical placement of objects, but the accentuation of the results of the verbal action.